2007
DOI: 10.1289/ehp.10056
|View full text |Cite|
|
Sign up to set email alerts
|

A Biomonitoring Study of Lead, Cadmium, and Mercury in the Blood of New York City Adults

Abstract: ObjectivesWe assessed the extent of exposure to lead, cadmium, and mercury in the New York City (NYC) adult population.MethodsWe measured blood metal concentrations in a representative sample of 1,811 NYC residents as part of the NYC Health and Nutrition Examination Survey, 2004.ResultsThe geometric mean blood mercury concentration was 2.73 μg/L [95% confidence interval (CI), 2.58–2.89]; blood lead concentration was 1.79 μg/dL (95% CI, 1.73–1.86); and blood cadmium concentration was 0.77 μg/L (95% CI, 0.75–0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
147
6
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(182 citation statements)
references
References 46 publications
21
147
6
8
Order By: Relevance
“…The geometric mean of the blood cadmium levels of men (1.57 lg/L) and women (1.49 lg/L) in KNHANES III is similar to that found in a 1992 field study of Korean subjects (Yeon et al 1992): 1.80 and 1.50 lg/L, respectively. Our geometric mean cadmium levels in both genders were slightly lower than those in the Japanese general population (Ikeda et al 1994(Ikeda et al , 2000aKurihara et al 2004) but were two-to fourfold higher than those in the US population (McKelvey et al 2007;Tellez-Plaza et al 2008) and other south Asian populations (Zhang et al 1999).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The geometric mean of the blood cadmium levels of men (1.57 lg/L) and women (1.49 lg/L) in KNHANES III is similar to that found in a 1992 field study of Korean subjects (Yeon et al 1992): 1.80 and 1.50 lg/L, respectively. Our geometric mean cadmium levels in both genders were slightly lower than those in the Japanese general population (Ikeda et al 1994(Ikeda et al , 2000aKurihara et al 2004) but were two-to fourfold higher than those in the US population (McKelvey et al 2007;Tellez-Plaza et al 2008) and other south Asian populations (Zhang et al 1999).…”
Section: Discussioncontrasting
confidence: 60%
“…Several previous surveys (Berode et al 1991;Pirkle et al 1994;Batariova et al 2006;Menke et al 2006;McKelvey et al 2007;Saraiva et al 2007) found that the blood lead levels were higher in men than in women due to higher lead exposure and higher blood hematocrit levels, which is due to lead in blood being bound to erythrocytes (WHO 1995;Vahter et al 2002). We also found that the blood lead level differed significantly with gender, being 30% higher in men than in women.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Other methods of sample preparation for blood are dilution with HNO 3 [9,10] or tetra methyl ammonium hydroxide (TMAH) [11]. Digestion of blood and serum samples was performed with HNO 3 by pressure ashing in an oven [12], by wet digestion with a mixture of HNO 3 /H 2 O 2 in glass vessels at 100 C [13], by UV digestion with HNO 3 /H 2 O 2 [14] or by microwave (MW)-assisted high-pressure digestion with HNO 3 [15].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Some of these applications have their focus on the analytical method development and the ensuing analytical problems [12,17,24], whereas other ICP-MS applications describe results of biomonitoring studies with an epidemiological and statistical discussion [27,30]. Both aspects may also be present [8,10,15,35].…”
Section: Multielemental Determinationsmentioning
confidence: 99%